2006
DOI: 10.1016/j.ydbio.2005.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cdx4 is a direct target of the canonical Wnt pathway

Abstract: There is considerable evidence that the Cdx gene products impact on vertebral patterning by direct regulation of Hox gene expression. Data from a number of vertebrate model systems also suggest that Cdx1, Cdx2 and Cdx4 are targets of caudalizing signals such as RA, Wnt and FGF. These observations have lead to the hypothesis that Cdx members serve to relay information from signaling pathways involved in posterior patterning to the Hox genes. Regulation of Cdx1 expression by RA and Wnt in the mouse has been well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
106
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 60 publications
9
106
0
Order By: Relevance
“…Activation of this regulatory module by the onset of gastrulation requires the activation and up-regulation of the Cdx genes. Multiple signals have been identified that contribute to Cdx expression including FGF, Wnt, BMP, and retinoic acid (Pillemer et al, 1998b;Houle et al, 2000;Keenan et al, 2006;Pilon et al, 2006). The surprising finding was that, initially, during late blastula, the Oct3/4 factors promote Cdx1 expression through up-regulation of FGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this regulatory module by the onset of gastrulation requires the activation and up-regulation of the Cdx genes. Multiple signals have been identified that contribute to Cdx expression including FGF, Wnt, BMP, and retinoic acid (Pillemer et al, 1998b;Houle et al, 2000;Keenan et al, 2006;Pilon et al, 2006). The surprising finding was that, initially, during late blastula, the Oct3/4 factors promote Cdx1 expression through up-regulation of FGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A second class contains many of the previously identified Wnt targets that are expressed ventrally or posteriorly. These genes are Gbx2 (von Bubnoff et al 1996), the Cdx group (Epstein et al 1997;Haremaki et al 2003;Shimizu et al 2005;Keenan et al 2006;Pilon et al 2006), the Vent/Vox/Ved/ Xom group (Gawantka et al 1995;Ladher et al 1996;Onichtchouk et al 1996;Schmidt et al 1996;Imai et al 2001;Ramel and Lekven 2004;Thorpe and Moon 2004), and the Meis group (Meis3) (Choe et al 2009;Elkouby et al 2010). The remaining genes include some known bone morphogenetic protein (BMP)-and fibroblast growth factor (FGF)-inducible genes, reiterating the importance of the cross talk between these pathways, and novel putative Wnt targets (Table 1).…”
Section: Putative Transcriptional Targets Of the Wnt Pathway In Axis mentioning
confidence: 99%
“…Loss of the Cdx4 gene function in the zebrafish mutant kugelig shows its essential role in posterior development (Davidson et al 2003). The promoterof the Xenopus and mammalian Cdx4 gene is Wnt inducible and contains multiple TCF/LEF binding sites (Haremaki et al 2003;Shimizu et al 2005;Pilon et al 2006). Up-regulation of Cdx genes causes the anterior shift of posterior markers in Xenopus and zebrafish (Isaacs et al 1998;Shimizu et al 2005;Faas and Isaacs 2009).…”
Section: Putative Transcriptional Targets Of the Wnt Pathway In Axis mentioning
confidence: 99%
“…The Cdx (caudal) and the Meis group genes, like Vent genes, are regulated by Wnt signaling during anteroposterior patterning [129][130][131] and contain multiple TCF-binding sites in their DNA regulatory elements [132][133][134]. Like Vent genes, these genes are also controlled by TCF3-mediated repression [79].…”
Section: Mechanisms Of Target Gene Regulationmentioning
confidence: 99%